Hubungan Antara Gegar Budaya Dengan Penyesuaian Sosial Siswa Papua di Magelang - Inosensia Dini Pramudiana; Theresia Dewi Setyorini (Soegijapranata Catholic University, 2019)
Abstract: The efforts to improve the quality of education in Papua is done through education scholarship program, and one of them is by sending senior high school students in Papua to other regions for education. The movement of the students to other regions forces them to do social adjustments. In this situation, each individual often experiences shocks to the new cultures (culture shock). This research was conducted to empirically test the relationship of culture shock with social adjustment of Papuan students in Magelang. The hypothesis in this study is that there is a negative relationship between culture shock and the social adjustment of Papuan students who migrated to Magelang. The higher the culture shock is experienced, the lower the social adjustment ability is, and vice versa. The results of this study indicate that the proposed hypothesis is proved, that the culture shock is negatively correlated and very significant to social adjustment. The analysis between the culture shocks and social adjustments shows a strong relationship between the four aspects (stress reaction, cognitive fatigue, role shock, and personal shock) in culture shock with social adjustment. Among those four aspects, role shock aspect has the highest correlation coefficient. This shows that this aspect is the most closely related to the social adjustment of Papuan students in Magelang, and the least related is the stress reaction. Keywords: culture shock, social adjustment, Papuan students Abstrak: Papua merupakan salah satu provinsi terkaya di Indonesia namun kualitas sumber daya di Papua masih rendah, tercatat Indeks Pembangunan Manusia di Papua tahun 2016 sebesar 57,25. Upaya untuk meningkatkan kulitas pendidikan di Papua dilakukan melalui program besiswa pendidikan, salah satunya dengan mengirim siswa SMA Papua keluar daerahnya untuk menempuh pendidikan. Pada masa ini siswa harus melakukan penyesuaian sosial. Penyesuaian sosial adalah kemampuan individu untuk berinteraksi secara sehat terhadap situasi sosial yang ada, sehingga mencapai kehidupan sosil yang menyenangkan. Dalam situasi ini, individu dapat mengalami kekagetan terhdap budaya yang baru (gegar budaya). Tujuan penelitian ini adalah untuk menguji secara empiric hubungan gegar budaya dengan penyesuaian sosial siswa Papua di Magelang. Hipotesis dari penelitian ini adalah ada hubungan negatif antara gegar budaya dengan penyesuaian sosial. Semakin tinggi gegar budaya, semakin rendah penyesuaian sosial, dan sebaliknya. Subyek dari penelitian ini adalah siswa Papua kelas XII dan XII di Magelang. Analisa data yang digunakan adalah uji korelasi Product Moment dengan menggunakan program SPSS (Statistical Packages for Social Sciences) seri 23.0. Analisa data menunjukan nilai r = -0,548 dan p = 0,000 (p